2019
DOI: 10.1101/713214
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inhibiting Mycobacterium tuberculosis ClpP1P2 by addressing the equatorial handle domain of ClpP1 subunit

Abstract: 19Unlike other bacterial ClpP systems, mycobacterial ClpP1P2 complex is essential 20 for mycobacterial survival. The functional details of Mycobacterium tuberculosis (Mtb) 21 ClpP1P2 remains largely elusive and selectively targeting ClpP of different species is a 22 big challenge. In this work, cediranib was demonstrated to significantly decrease the 23 activity of MtbClpP1P2. By solving the crystal structure of cediranib-bound 24 MtbClpP1P2, we found that cediranib dysregulates MtbClpP1P2 by interfering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Peptide boronates have been shown to also directly engage MtClpP1P2 active sites, causing inhibition at low-micromolar concentrations and preventing growth of M. tuberculosis (34)(35)(36). More recently, Cediranib, an anticancer drug, was proposed as a novel noncovalent inhibitor of MtClpP1P2 (37).…”
Section: Significancementioning
confidence: 99%
“…Peptide boronates have been shown to also directly engage MtClpP1P2 active sites, causing inhibition at low-micromolar concentrations and preventing growth of M. tuberculosis (34)(35)(36). More recently, Cediranib, an anticancer drug, was proposed as a novel noncovalent inhibitor of MtClpP1P2 (37).…”
Section: Significancementioning
confidence: 99%
“…Interestingly, this conformational change could be reversed and activity partially restored by ADEP binding. More recently Cediranib, an anti-cancer drug, was shown to bind to a hydrophobic pocket at the interface of the head and handle domains of MtClpP1, leading to inhibition of the MtClpP1P2 complex(37).Our study provides an important step towards the goal of manipulating MtClpP1P2 function by providing the structural basis for why this complex is catalytically dead in the absence of activator peptides and why, unlike for many other ClpPs, binding of ADEPs do not activate the protein.The 3.0 Å resolution structure from cryo-EM of the apo-form of MtClpP1P2 shows that the complex is in the compact conformation. The hallmarks of the compact form are truncated handle helices and disordered handle β-strands that lead to an impaired catalytic triad, thereby explaining the lack of activity observed for apo-state of the complex.…”
mentioning
confidence: 83%
“…Caseinolytic Protease (ClpP) Caseinolytic protease (ClpP) is a tetradecameric protein considered a bacterial target for drug design (Figure 2). At pH 7.6 (phosphate buffer), ClpP shows a moderate stability (unfolding temperature of 62 • C, which was further increased to 83 • C in the presence of 100 µM bortezomib, a boronic proteasome inhibitor) [24]. It has been reported that ClpP can be activated by inhibitors binding in the active site, a finding difficult to explain.…”
Section: Monod-wyman-changeux (Mwc) Modelmentioning
confidence: 99%